A retrospective analysis of the respiratory adjusted shock index to determine the presence of occult shock in trauma patients. Issue 4 (April 2018) - Caputo, Nicholas; Reilly, James; Kanter, Marc; West, Jason
Abstract : BACKGROUND: The shock index (SI), calculated as hear rate/systolic blood pressure, is a simple hemodynamic marker that may be used to assess for the presence of occult shock in trauma patients. The normal range for a healthy adult patient is 0.5 to 0.7. Recently, studies have demonstrated that tachypnea is the most important predictor of cardiac arrest in hospital wards and is an important indicator of derangements across multiple organ systems. As such, we have sought to determine whether the inclusion of the patient's respiratory rate (RR) to the already existing SI (called the Respiratory Adjusted Shock Index [RASI]), calculated as hear rate/systolic blood pressure*(RR/10), will improve the overall diagnostic accuracy of detecting patients in early occult shock. METHODS: A retrospective chart review over a 4-year period (2012–2016) at an urban, Level I trauma center was performed. All patients admitted to hospital for trauma were included in the study. Exclusion criteria were patients in traumatic arrest or in overt shock. Charts were reviewed for triage vital signs and point of care lactate drawn within 30 minutes of presentation. A lactate greater than 2 mmol/L was used to determine presence of hypoperfusion. The upper limit of normal for the RASI was calculated by multiplying the upper limit of the SI by 1.9 (RR of 19 divided by 10) and validated internally. RESULTS: A total of 3, 093 patients were included in this study. There was no difference in SI for patients discharged versus patients admitted, 0.6 (95% CI, 0.5–0.7) versus 0.7 (95% CI, 0.5–0.8) and a significant difference between the same groups of patients (discharged vs. admitted) for the RASI, 1.1 (95% CI, 1.04–1.18) versus 1.46 (95% CI, 1.35–1.55), respectively. Area under the curve for SI was 0.58 and for the RASI score was 0.94. CONCLUSION: The RASI score improves diagnostic accuracy for detecting early occult shock in trauma patients when compared to the SI. LEVEL OF EVIDENCE: Diagnostic, level II.